Kdo se boji slovenščine? - Grgič, Matejka (Teorija in praksa, 2020)
In this paper, I discuss certain sociolinguistic and resultant linguistic features of the Slovenian-speaking community that defines itself as a Slovenian minority/autochthonous community in Italy. I focus on individual cases of language policies, language planning and implementations of strategies to promote Slovenian, while also highlighting the deficiencies therein. I also examine certain ideological choices and consequences of the lack of comprehensive expert strategies in this area. The paper presupposes that language politics is too often confined to the planning, processing and strengthening of the formal legal status of the minority language in relation to the majority language. The relationship between the so-called motivators and hygiene factors is significantly imbalanced in favour of the latter, as reflected in the everyday communication practices of the speakers, their language repertoire and, finally, the ways they characterise their own language and identity
Keywords: identiteta; Italija; Jezikovna politika; jezikovno načrtovanje; Language policy; Slovene language; Slovenščina; sociolingvistika; zamejski Slovenci